Taxonomy of the Proisotoma complex. IV. Notes on chaetotaxy of femur and description of new species of Scutisotoma and Weberacantha from Asia - Huang, Cheng-Wang; Potapov, Mikhail (Zootaxa, 2012)
Four new species of the genera Scutisotoma Bagnall and Weberacantha Christiansen are described from Asia; S. bengeisp.nov. (SW China), S. robustodens sp.nov. (East Siberia), S. trichaetosa sp.nov. (E China), and W. cylindrica sp. nov.(Far East of Russia). Scutisotoma christiansensi (Stach, 1959) is figured from type material. The chaetotaxy of femur offirst pair of legs is given a consistent nomenclature, its variability based on a survey of 31 species of two genera is studied. The genus Scutisotoma is divided into three species groups (christianseni, schisti, and subarctica).